A Rare Case of Guillain–Barré Syndrome with Signs of Meningeal Irritation and Treatment-Related Fluctuations/Relapse - Singh, Kushagra; Lohiya, Sham; Chaudhary, Richa; Lakra, Mahaveer; Damke, Sachin (Journal of Pediatric Neurology, 2022)
Guillain–Barré Syndrome is an acute inflammatory demyelinating polyradiculoneuropathy that can present at any age. The presentation of Guillain–Barré syndrome may be variable as the classic symptoms of areflexia and flaccid paralysis may or may not be present. Here we reported a case of a 15-year-old male patient who presented with complaints of weakness in bilateral lower limbs with inability to sit along with slurred speech and drooling of saliva with positive meningeal signs like neck stiffness and Kernig's sign. His symptoms improved with immunoglobulin therapy. Five days later, the child again had pain and increased weakness with increased work of breathing for which repeat dose and course of immunoglobulins were given. As patients with signs of meningeal irritation may suggest other diseases such as meningitis, it is important to consider atypical cases of Guillain–Barré syndrome along with treatment-related fluctuations as observed in our patient.
Keywords: meningeal signs; treatment-related fluctuations; polyradiculoneuropathy